Green Technologies for Environmental Air and Water Impact Reduction in Ships: A Systematic Literature Review - Edwin Paipa-Sanabria; Daniel González-Montoya; Jairo R. Coronado-Hernández (Journal of Marine Science and Engineering)
This study reviews various green technological strategies integrated into vessels to mitigate environmental impact, focusing on atmospheric pollution and marine environment protection. The research is based on a systematic review of academic literature published between 2019 and 2024, using the Scopus and Web of Science databases and applying PRISMA criteria. The findings reveal that the main environmental issues in the naval sector include greenhouse gas emissions, harmful discharges, and invasive species that affect marine biodiversity. The analysis is framed within international regulations such as those established by the IMO and classification societies, where the most relevant indicators identified are the EEDI and EEXI. However, the results of this review emphasize that, while these regulations are fundamental, it is necessary to analyze further the technical and economic barriers affecting the widespread implementation of these technologies and develop incentive mechanisms that facilitate their adoption across different vessel types and sizes. Promising solutions include alternative fuels, new propulsion systems, and emission-reduction technologies. The conclusion underlines that although the sector is transitioning toward sustainability, economic and widespread implementation challenges remain.